Pengaruh Elektrodeposisi Nanopartikel Perak pada Elektroda Reduced Graphene Oxide terhadap Stabilitas Superkapasitor - Pratiwi Sanggusti; Nur hayati; Nina Aprilini; Rahmat Hidayat; Harman Amir; Hidayat Hidayat; Maria Ulfa; Yahdi Bin Rus (Lembaga Pengembangan Kinerja Dosen, 2026)
Supercapacitors have attracted considerable attention as energy storage devices owing to their high power density, rapid charge–discharge capability, and long cycle life. However, the electrochemical performance of reduced graphene oxide (rGO) is limited by the restacking phenomenon, which decreases the active surface area and restricts electrolyte ion diffusion. This study investigates the effect of silver (Ag) nanoparticle deposition on the stability of rGO electrodes using an electrodeposition method. Ag nanoparticles were deposited from a 5 mM AgNO₃ solution and the resulting electrodes were characterized by Scanning Electron Microscopy (SEM). Their electrochemical performance was evaluated using Cyclic Voltammetry (CV) and cycling stability tests up to 1,000 cycles. SEM analysis confirmed the successful and relatively homogeneous distribution of Ag nanoparticles on the rGO surface. The electrochemical results showed that the rGO/Ag electrode retained approximately 96–97% of its initial capacitance after 1,000 cycles, whereas the pristine rGO electrode retained only about 69%. These findings demonstrate that Ag deposition effectively enhances the structural stability and electrochemical performance of rGO electrodes, indicating their potential for high-performance supercapacitor applications.